Quality of systematic reviews on the treatment of vesiculobullous skin diseases. A meta-epidemiological study - Kamilla Mayr Martins Sá; Juliana Cavaleiro Rodrigues; Lígia Borges da Silva; Giovanna Marcılio Santos; Mileny Esbravatti Stephano Colovati; Ana Luiza Cabrera Martimbianco (Sociedade Brasileira de Dermatologia, 2024)
Abstract Background Systematic reviews of Randomized Controlled Trials (RCTs) are considered high-level evidence to support a decision on therapeutic interventions, and their methodological quality is essential to provide reliable and applicable results. Objective This meta-epidemiological study aimed to map and critically appraise systematic reviews assessing treatments for vesiculobullous skin diseases. Methods We conducted a comprehensive search strategy on MEDLINE (via Pubmed) in December 2022 without restrictions to find systematic reviews evaluating pharmacological interventions for vesiculobullous skin diseases. The methodological quality was assessed using the AMSTAR-2 tool, and additional information was extracted. We identified nine systematic reviews published between 2002 and 2021, seven assessing pemphigus. Results According to the AMSTAR-2 tool, 55.6% were classified as critically low quality, 22.2% as moderate quality, 11.1% as low and 11.1% as high quality. No review assessed the certainty of the evidence (GRADE); 86% of pemphigus reviews had at least two overlapping RCTs. There were some limitations regarding methodological flaws and the AMSTAR-2 tool use Conclusions These findings reveal a frail methodological quality of systematic reviews about vesiculobullous diseases treatment that may impact the results. Therefore, methodological rigor is mandatory for future systematic reviews to avoid duplication of effort and increase the certainty of the evidence supporting decision-making.